Effect of Welding Heat Input on the Microstructure and Impact Toughness of HAZ in 420 MPa-Grade Offshore Engineering Steel - Liu, Dekun; Yang, Jian; Zhang, Yinhui; Qiu, Yunlong; Cheng, Guoguang; Yao, Meiyi; Dong, Jianxin (Frontiers in Materials, 2021)
In the present work, the effect of the welding heat input on the microstructure, martensite–austenite (M–A) constituents, and impact toughness of the coarse-grained heat-affected zone (CGHAZ) in offshore engineering steel with Ca deoxidation is studied. With the heat input increased from 50 to 100 kJ/cm, the HAZ toughness decreased rapidly, while the measured microhardness decreases steadily. The grain sizes are increased from 52 to 132 μm, and the width of bainite lath increased from 0.4 to 2 μm. The area fraction of lath bainite (LB) decreased, while the area fraction of granular bainite (GB) increased. The average width of M–A constituents grows from 0.3 to 0.6 μm, and the average length grows from from 0.5 to 0.9 μm. Its area fraction is increased from 5.3 to 8.6% and then decreased to 6.1%, and its number density decreased from 0.7 to 0.2 μm−2. The morphologies of M–A constituents change from dot-like to slender and blocky, which are deleterious to impact toughness. The fracture mechanism changes from ductile to quasicleavage and cleavage as the heat input is increased. As the M–A constituents are always found as the cleavage initiation, they should be responsible for the decrease in HAZ toughness when the heat input is above 100 kJ/cm.